Using (disruptive) eco-visualization to re-connect humans to nature: results from workshops with youth and adults - Löfström, Erica; Santandrea, Chiara; Hellevik, Christina Carrozzo (Frontiers in Psychology, 2025)
In the Anthropocene epoch, opportunities for nature connectedness are diminishing, raising concerns for both individual well-being and the nurturing of environmental mindfulness in upcoming generations. The prevailing discussion emphasizes the urgency of strengthening our connection with nature, but this viewpoint still largely treats nature as a resource for human benefit. We believe that this human-centered perspective needs re-evaluation, and that a major shift of our understanding of the earth’s ecosystems and our role in it may be necessary. In this study we bring together the latest environmental science assessments on planetary health with eco-critical research and the field of design. We explore how non-technological and technological interventions can facilitate a reconnection with nature. With the ambition to not only evoke emotional resonance with nature, but to also use this as a starting point for collective reflections and joint co-creation of a more sustainable future, we endeavor into a transformative approach. As a first step, we carried out two explorative reflection workshops with different stakeholders: one in a rural setting and one in an urban one, using transformative experiences (disruptive eco-visualizations) as interventions with the intent to evoke an emotional response amongst the workshop participants. This emotional response was used as a starting point for reflections on our current and potential future role as humans in the eco-system. The results show that the participants in the first workshop achieved a reconnection with nature, but some also showed signs of biophobia. In the second workshop, the young participants showed a very cynical view of the future of humanity through the use of art and sense of humor. These results point to the fact that it is more urgent than ever to find ways to reconnect people with nature, especially young adults, to counter the effects of eco-anxiety.